2021
DOI: 10.1186/s13287-021-02529-w
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human umbilical cord mesenchymal stem cells to treat premature ovarian failure

Abstract: As one of the problems and diseases for women before 40 years, premature ovarian failure (POF) could be characterized by amenorrhea, low estrogen levels, infertility, high gonadotropin levels, and lack of mature follicles. Causes of the disease involve some genetic disorders, autoimmunity diseases, and environmental factors. Various approaches have been employed to treat POF, however with limited success. Today, stem cells are used to treat POF, since they have the potential to self-repair and regenerate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 198 publications
(244 reference statements)
0
67
0
Order By: Relevance
“…In this study, HUCMSCs promoted cell growth, increased the number of EdU cell and cell metastasis, and reduced caspase-3/9 activity levels in the in vitro model. Shareghi-Oskoue et al showed that HUCMSCs could treat premature ovarian failure [ 21 ]. These data indicated that HUCMSCs promoted cell recovery to improve premature ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, HUCMSCs promoted cell growth, increased the number of EdU cell and cell metastasis, and reduced caspase-3/9 activity levels in the in vitro model. Shareghi-Oskoue et al showed that HUCMSCs could treat premature ovarian failure [ 21 ]. These data indicated that HUCMSCs promoted cell recovery to improve premature ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although it cannot directly differentiate to the oocyte, transplantation MSCs can secrete cytokines, signal, and growth factors to promote stem cells such as ESCs, iPSCs, and OSCs in artificial ovary differentiate into oocytes ( 92 ). MSCs can also simultaneously support nutrition and immune regulation for the ovary ( 93 ). It was reported that transplantation of MSCs can provide nearly 109 cytokines in the ovary to help recover follicles in POF patients ( 94 ).…”
Section: Additives For Transplantable and Functional Artificial Ovarymentioning
confidence: 99%
“…The adult Sprague-Dawley(SD) rats were purchesed from Hunan SJA Laboratory Animal Co., Ltd in China for reproduction rat pups. The rats were fed and watered freely in the SPF animal laboratory for 12 h day/night cycle, temperature (23)(24)(25)℃ and humidity (45-60%). A total of 80 rat pups were borned by adult SD rats and used for CP model.…”
Section: Animal Ethics Selection and Welfarementioning
confidence: 99%
“…The HUCMSCs from passage numbers 0-5 were characterized with ow cytometry (Becton, Dickinson and Company, USA). The cells were added with rabbit polyclonal antibodies conclude CD73, CD44 ,CD90 ,CD105 ,CD34,CD45,HLA-DR (Proteintech Inc,USA) ( 1:100 dilution) to detect the surface antigens of HUCMSCs [23].…”
Section: Isolation and Characterization Of Hucmscsmentioning
confidence: 99%